PERAN INKRIMENTAL KEPALA SEKOLAH DALAM PENGAMBILAN KEPUTUSAN EFEKTIF DI SMK NEGERI 1 PARIAMAN - Yulfianti, Yulfianti; Marlin, Yessy; Marsidin, Sufyarma; Irsyad, Irsyad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study explores the principal's incremental contribution to effective decision-making at SMK Negeri 1 Pariaman. Principal leadership in vocational education institutions faces complex challenges: how to meet educational demands while addressing the ever-changing needs of business and industry. The incremental strategy introduced by Lindblom emphasizes a decision-making process that takes place through small, gradual steps, which differs from the rational-comprehensive approach that requires in-depth analysis. This study adopted a qualitative method through content analysis of various school policy documents such as the RKS (Regional Work Plan), RKAS (Regional Work Plan), meeting minutes, and official decisions from the principal. The research findings indicate that the implementation of the incremental approach by the principal has proven effective in minimizing the risk of uncertainty, increasing the school's flexibility and adaptability, facilitating organizational learning, and strengthening accountability and leadership legitimacy. This approach provides schools with the opportunity to quickly adapt policies without the need for significant and high-risk changes, creating a strong and innovative school climate in the face of both internal and external change.